Approach to Feed Drive Load Measurements in Heavy Turning - Paweł Medyk; Marcin Kasprzak (Journal of Machine Engineering)
It is well known that the forces loading the feed axes carry a lot of information about the machining process. The measurement of the forces opens up the possibility of implementing such functions as cutting tool condition diagnosis, tool breakage detection and adaptive feed control aimed at maintaining constant loading. Hence inexpensive, but usable in industrial conditions, force sensors are sought for the steerable axes. The article describes a feed drive load measuring system based on industrial force sensors. These are strain gauge sensors located in the ball screw area. The system was designed for compressive and tensile forces of up to 30 kN. Also the effect of nonaxial forces on the measurement error is examined. The proposed system does not introduce any new elements into the machine structure and requires only its minor modifications. The system was tested in a strength testing machine.